2023
DOI: 10.1186/s40780-023-00274-1
|View full text |Cite
|
Sign up to set email alerts
|

Prescription factors influencing baloxavir prescription during the 2018/2019 and 2019/2020 seasons: a administrative database study in Japan

Abstract: Background We aimed to evaluate the factors associated with baloxavir prescription in Japanese hospitals using a health insurance claim-based database (MDV analyzer), during the 2018/2019 and 2019/2020 influenza seasons. The MDV analyzer contains anonymized claims data from approximately 420 Diagnosis Procedure Combination hospitals, and does not contain data from clinics. Methods Data were collected for influenza patients treated with anti-influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…We concurrently evaluated trends in drug prescription and ADR reporting and found that after the revision of the oseltamivir package insert, the number of prescriptions, but not the number of reports of abnormal behavior, increased. As previous studies have also shown that new anti-influenza drugs and their dosage forms might have influenced prescription trends in recent years [ 11 ], we will continue to focus on future trends.…”
Section: Discussionmentioning
confidence: 99%
“…We concurrently evaluated trends in drug prescription and ADR reporting and found that after the revision of the oseltamivir package insert, the number of prescriptions, but not the number of reports of abnormal behavior, increased. As previous studies have also shown that new anti-influenza drugs and their dosage forms might have influenced prescription trends in recent years [ 11 ], we will continue to focus on future trends.…”
Section: Discussionmentioning
confidence: 99%